Overestimation of the second time interval replaces time-shrinking when the difference between two adjacent time intervals increases - Nakajima, Yoshitaka; Hasuo, Emi; Yamashita, Miki; Haraguchi, Yuki (Frontiers in Human Neuroscience, 2014)
When the onsets of three successive sound bursts mark two adjacent time intervals, the second time interval can be underestimated when it is physically longer than the first time interval by up to 100 ms. This illusion, time-shrinking, is very stable when the first time interval is 200 ms or shorter (Nakajima et al., 2004, Perception, 33). Time-shrinking had been considered a kind of perceptual assimilation to make the first and the second time interval more similar to each other. Here we investigated whether the underestimation of the second time interval was replaced by an overestimation if the physical difference between the neighboring time intervals was too large for the assimilation to take place; this was a typical situation in which a perceptual contrast could be expected. Three experiments to measure the overestimation/underestimation of the second time interval by the method of adjustment were conducted. The first time interval was varied from 40 to 280 ms, and such overestimations indeed took place when the first time interval was 80-280 ms. The overestimations were robust when the second time interval was longer than the first time interval by 240 ms or more, and the magnitude of the overestimation was larger than 100 ms in some conditions. Thus, a perceptual contrast to replace time-shrinking was established. An additional experiment indicated that this contrast did not affect the perception of the first time interval substantially: The contrast in the present conditions seemed unilateral.